Evaluating the risk of spread of H5N1 highly pathogenic avian influenza in Kenya - Bett, Bernard K.; Hansen, F.; Onkundi, D.; Costard, Solenne; Randolph, Thomas F.; Pfeiffer, Dirk U. (International Livestock Research Institute, 2011)
Outbreaks of H5N1 highly pathogenic avian influenza (HPAI) occurred in 11 countries in Africa between the years 2006 – 2008. Kenya did not get exposed to the disease but as the perceived risk of introduction of the HPAI virus heightened, the demand for poultry and poultry products waned. This resulted in enormous economy-wide impacts. To generate information that could be used for improving the contingency plans that had been developed by the Department of Veterinary Services, we assessed the risk of spread of the disease in the country using a spatial simulation model; the model used data on topography, landscape features, and vegetation and road networks in a spatial lattice of 1 square km. In parallel, we constructed risk maps for the introduction and the spread of HPAI. The results of the simulation model and the risk maps agree that the areas of Nairobi, Mombasa and Nyanza show the highest risk for the spread of the disease. We also conducted a qualitative risk assessment study involving small scale commercial (sector 3) and backyard (sector 4) poultry farms to identify poultry production practices that could be associated with the release or exposure of the virus at the farm-level. The model identified the ports of Mombasa and the JKIA as potential gateways of introduction of the disease. It also revealed that densely populated areas, e.g. cities, had higher risk of experiencing outbreaks compared to sparsely populated ones. Similarly, areas that have dense road networks had higher risk of experiencing outbreaks. Qualitative risk assessment studies indicated that the risk of transmission of the disease from an infected backyard farm was higher than that from an infected small scale commercial farm due to poor biosecurity practices practised in such farms. Free-range production systems in backyard poultry farms, for example, allow unlimited contact between poultry and “farm-bridge” animals and birds. All these studies identified geographical zones and farm practices that should be targeted for surveillance. They also identified areas for further research.